A photoelectric sensor based on bismuth sulfide composite material and its application in norfloxacin detection
Through the photoelectric sensor based on bismuth sulfide composite material, combined with the modification of nano-gold particles and tin fluorine-oxidized glass electrode, the problem of low detection efficiency and high cost of norfloxacin in the existing technology is solved, and efficient and sensitive detection effect is achieved .
Patent Information
- Application Number
- CN202411169420.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-24
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-08-24
AI Technical Summary
The existing photoelectrochemical technology is relatively low in norfloxacin detection, and the instrument costs are high and the experimental process is complex.
Using a photoelectric sensor based on bismuth sulfide composite material, an efficient photoelectric sensor is constructed through the modification of bismuth composite material and nano-gold particles and the modification of fluorine tin oxide glass electrode, combined with the modification of norfloxacin aptamer.
The detection effect of norfloxacin with high photoelectric response, rapid detection, high sensitivity, wide linear range, low detection limit and strong selectivity is achieved, reducing the detection cost and experimental complexity.
Smart Images

Figure CN119125034B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photoelectric sensors, and in particular to a photoelectric sensor based on a bismuth sulfide composite material and application thereof in the detection of norfloxacin. Background Art
[0002] Norfloxacin (NOR) is a broad-spectrum antibiotic belonging to the quinolone class of drugs. It is commonly used to treat infections caused by bacteria, such as urinary tract infections, respiratory tract infections, digestive tract infections, and skin and soft tissue infections. Norfloxacin inhibits bacterial DNA metabolism, blocks bacterial DNA replication and synthesis, and thus kills or inhibits bacterial growth. It has high bioavailability and wide tissue distribution, which makes norfloxacin show significant advantages in the treatment of various infections. In addition, norfloxacin is also widely used in the veterinary field, and there has not yet been a large-scale drug resistance problem, so the risk of drug resistance is low. However, the abuse of norfloxacin also has certain risks. Excessive intake of food containing norfloxacin residues may cause harm to human health, including allergic reactions, liver and kidney damage, and digestive system problems. In addition, during the metabolism and excretion of veterinary drugs in animals, norfloxacin and its metabolites may enter the environment, pollute the soil, water and air, affect the ecosystem, and destroy the ecological balance. Therefore, it is also crucial to establish a suitable analytical method for detecting norfloxacin in water samples and dairy products.
[0003] At present, the analytical method based on high performance liquid chromatography-mass spectrometry has been developed to maturity, which has high sensitivity and excellent selectivity. However, the technology still has problems such as high instrument cost and complex experimental process. In recent years, electrochemical analysis has been rapidly developed, which has high sensitivity and good selectivity, and therefore has been used in drug residue detection. Bismuth sulfide and bismuth selenide are widely used in photoelectrochemistry because they both have excellent photoelectric properties. However, the shape of bismuth sulfide crystals is usually relatively simple, and the electron transfer rate of bismuth sulfide is slow, resulting in its application in photoelectrochemical reactions. The efficiency is relatively low.
[0004] Therefore, according to the above-mentioned related technologies, it is urgent to develop a photoelectric sensor based on bismuth sulfide composite materials and its application in the detection of norfloxacin. Summary of the invention
[0005] In view of this, the purpose of the present invention is to propose a photoelectric sensor based on a bismuth sulfide composite material and its application in the detection of norfloxacin. The sensor has the advantages of high photoelectric response, rapid and sensitive detection, and can be used for the detection of norfloxacin residues in water and dairy products.
[0006] Based on the above objectives, the present invention provides a photoelectric sensor based on a bismuth sulfide composite material and its application in the detection of norfloxacin.
[0007] A photoelectric sensor based on a bismuth sulfide composite material, the preparation method of the photoelectric sensor is as follows:
[0008] Step S1. Preparation of bismuth composite material;
[0009] Step S2. modifying the bismuth composite material with gold nanoparticles to obtain composite material 1;
[0010] Step S3. Modification of the fluorine-doped tin oxide glass electrode to obtain a modified electrode 1;
[0011] Step S4: modifying the modified electrode 1 with the norfloxacin aptamer to obtain a photoelectric sensor.
[0012] Preferably, the preparation process of the bismuth composite material in step S1 is as follows:
[0013] Step A1. Disperse bismuth nitrate powder in ethylene glycol and stir ultrasonically for 10-15 min to obtain solution A;
[0014] Step A2. Disperse sodium sulfide in ultrapure water and stir ultrasonically for 15-20 min to obtain solution B;
[0015] Step A3. Dispersing urea in ultrapure water to obtain solution C;
[0016] Step A4. Add solution B dropwise to solution A to form a black suspension, and then add solution C to obtain a mixed solution D;
[0017] Step A5. Add bismuth selenide solid to the mixed solution D and stir for 30 min to obtain a mixed solution E;
[0018] Step A6. Transfer the mixed solution E into a polytetrafluoroethylene-lined autoclave, heat it at 160-180°C for 8-12 hours, cool it to room temperature after the reaction, centrifuge it at 4100-4300 rpm for 10-15 minutes, remove the supernatant, wash it with water and anhydrous ethanol three times each, and then bake it in an oven at 60°C for 8-12 hours to obtain a bismuth composite material.
[0019] Preferably, the dosage ratio of the bismuth nitrate powder and ethylene glycol in step A1 is 0.9-1 g:12-15 mL, and the bismuth nitrate is bismuth nitrate pentahydrate powder.
[0020] Preferably, the usage ratio of the sodium sulfide and ultrapure water in step A2 is 0.6-0.7 g: 20-30 mL, and the sodium sulfide is solid sodium sulfide nonahydrate.
[0021] Preferably, the usage ratio of urea and ultrapure water in step A3 is 0.65-0.7 g: 10-12 mL.
[0022] Preferably, the volume ratio of solution A, solution B and solution C in step A4 is 12-15:20-30:10-12.
[0023] Preferably, the ratio of the mixed solution D to the bismuth selenide solid in step A5 is 42-57 mL: 1.2-1.3 g.
[0024] Preferably, the preparation process of the composite material 1 in step S2 is as follows:
[0025] Step B1. Heat the tetrahydrate chloroauric acid solution to boiling under stirring, then add sodium citrate solution dropwise until the solution changes from colorless to ink color and then to purple red, cool to room temperature, and purify with a dialysis bag for 22-24 hours to obtain nano gold sol;
[0026] Step B2: Disperse the bismuth composite material in the nano-gold sol and disperse by ultrasonic to obtain the composite material 1.
[0027] Preferably, the concentration of the tetrahydrate chloroauric acid solution in step B1 is 0.01%, the molecular weight cutoff MWCO of the dialysis bag is 500Da, the water is replaced every 4 hours during the purification process, for a total of 6 times, and the concentration of the sodium citrate solution is 10mM.
[0028] Preferably, in step B2, the dosage ratio of the bismuth composite material to the nano-gold sol is 14-16 mg: 4-6 mL, and the ultrasonic dispersion time is 50-60 min.
[0029] Preferably, the preparation process of the modified electrode 1 in step S3 is as follows:
[0030] The composite material 1 suspension was dripped onto a fluorine-doped tin oxide glass electrode and dried at 120° C. to obtain a modified electrode 1.
[0031] Preferably, the amount of the composite material 1 suspension is 34-36 μL.
[0032] Preferably, the norfloxacin aptamer in step S4 is thiol-modified norfloxacin.
[0033] Preferably, the process of modifying the norfloxacin aptamer in step S4 is as follows:
[0034] Step C1. dissolving the norfloxacin aptamer in a buffer solution at pH=8 to obtain a mixed solution F, and incubating the mixed solution F and the modified electrode 1 at room temperature for 50-60 minutes to obtain a modified electrode 2;
[0035] Step C2. drop the mixed solution F onto the surface of the modified electrode 2, and incubate at -4°C for 24 h under 100% humidity to obtain the modified electrode 3;
[0036] Step C3. Incubate the surface of the modified electrode 3 with 6-mercaptohexanol, and finally rinse with a buffer solution at pH=8 to obtain a photoelectric sensor.
[0037] Preferably, the concentration of the norfloxacin aptamer in step C1 is 100 nM, and the incubation process in step C1 is to allow the norfloxacin aptamer to be fully adsorbed on the surface of the modified electrode 1 .
[0038] Preferably, the amount of the mixed solution F in step C2 is 34-36 μL, and the incubation process in step C2 is to ensure that the norfloxacin aptamer is firmly fixed on the surface of the modified electrode 2 .
[0039] Preferably, the amount of 6-mercaptohexanol used in step C3 is 8-12 mL, and the concentration of 6-mercaptohexanol is 1 mM. The incubation process in step C3 is to block the unmodified area of the modified electrode 3 and prevent the specific adsorption of other reagents. The role of 6-mercaptohexanol is to form a thiol group with the surface of the modified electrode 3, thereby providing a surface compatible with nanogold, which helps to enhance the binding force between the norfloxacin aptamer and the nanogold particles. Finally, the buffer solution is used for washing to ensure that any unbound molecules are removed to obtain a photoelectric sensor.
[0040] The invention discloses an application of a photoelectric sensor based on a bismuth sulfide composite material in the detection of norfloxacin. The photoelectric sensor is used to detect norfloxacin in domestic water and milk.
[0041] Preferably, the photoelectric sensor is used to detect norfloxacin in domestic water, and the process is as follows:
[0042] Step D1. Incubation of the photosensor and the norfloxacin aptamer;
[0043] Step D2. Incubating the photosensor modified with the norfloxacin aptamer and norfloxacin;
[0044] Step D3. Sample pretreatment: pre-treat domestic water;
[0045] Step D4. measuring the recovery rate of the sample addition;
[0046] Preferably, the incubation process in step D2 is as follows: according to the specific binding reaction between the norfloxacin aptamer and the target, after incubation for 90 minutes, the photoelectric sensor modified with the prepared norfloxacin aptamer is used for current testing after washing with a PBS buffer solution, and is used to analyze and detect norfloxacin standard samples of different concentrations, and a norfloxacin concentration standard curve is drawn;
[0047] Preferably, the current test refers to the current measurement of the three-electrode system using a CHI-660E electrochemical workstation and the IT method, with the prepared photoelectric sensor as the working electrode, the platinum wire as the counter electrode, and Ag / AgCl as the reference electrode; all tests are performed at room temperature and repeated 3 times, and the electrolyte solution used is a phosphate buffered saline solution, and the pH of the phosphate buffered saline solution is 7.2;
[0048] Preferably, the process of drawing the standard curve of norfloxacin concentration is as follows: the photoelectric sensor modified with the norfloxacin aptamer is incubated with standard samples of norfloxacin of different concentrations at room temperature in the dark for 90 minutes to obtain a standard solution with a norfloxacin concentration range of 0.2-100 μM, and after washing with PBS buffer solution, an electrochemical workstation is used to perform a current test, and then the photoelectric signal is linearly fitted with the norfloxacin concentration to obtain a standard curve diagram.
[0049] Preferably, the pre-treatment process in step D3 is as follows:
[0050] Pretreatment of domestic water: The domestic water was ultrasonically treated for 15 min, then centrifuged at 4200 rpm for 10 min, and the supernatant was filtered through a 0.22 μm filter membrane.
[0051] The measurement process described in step D4 is as follows: adding norfloxacin at concentrations of 0.001 ng / mL, 0.1 ng / mL and 10 ng / mL to the domestic water sample, incubating with the norfloxacin aptamer-modified photoelectric sensor for 90 minutes, performing a current test, and calculating the recovery rate.
[0052] Preferably, the photoelectric sensor is used to detect norfloxacin in milk, and the process is as follows:
[0053] Step E1. Incubation of photosensor and norfloxacin aptamer;
[0054] Step E2. Incubating the photosensor modified with the norfloxacin aptamer and norfloxacin;
[0055] Step E3. Sample pretreatment: pre-treat domestic water;
[0056] Step E4. measuring the recovery rate of the sample addition;
[0057] Preferably, the incubation process in step E2 is as follows: according to the specific binding reaction between the norfloxacin aptamer and the target, after incubation for 90 minutes, the aptamer is washed with a PBS buffer solution and can be used for current testing, and the prepared norfloxacin aptamer-modified photoelectric sensor is used to analyze and detect norfloxacin standard samples of different concentrations, and a norfloxacin concentration standard curve is drawn;
[0058] Preferably, the current test refers to the current measurement of the three-electrode system using a CHI-660E electrochemical workstation and the IT method, with the prepared photoelectric sensor as the working electrode, the platinum wire as the counter electrode, and Ag / AgCl as the reference electrode; all tests are performed at room temperature and repeated 3 times, and the electrolyte solution used is a phosphate buffered saline solution, and the pH of the phosphate buffered saline solution is 7.2;
[0059] Preferably, the process of drawing the standard curve of norfloxacin concentration is as follows: the photoelectric sensor modified with the norfloxacin aptamer is incubated with standard samples of norfloxacin of different concentrations at room temperature in the dark for 90 minutes to obtain a standard solution with a norfloxacin concentration range of 0.2-100 μM, and after washing with PBS buffer solution, an electrochemical workstation is used to perform a current test, and then the photoelectric signal is linearly fitted with the norfloxacin concentration to obtain a standard curve diagram.
[0060] Preferably, the pre-processing process in step E3 is as follows:
[0061] Pretreatment of milk: acetonitrile was added to the milk for protein precipitation, and then the mixed suspension was subjected to ultrasonic treatment for 15 min, followed by centrifugation at 4200 rpm for 10 min, and the supernatant was filtered through a 0.22 μm filter membrane.
[0062] The measurement process described in step E4 is as follows: adding norfloxacin at concentrations of 0.001 ng / mL, 0.1 ng / mL and 10 ng / mL to the milk sample, incubating with the photosensor modified with the norfloxacin aptamer for 90 minutes, performing a current test, and calculating the recovery rate.
[0063] Beneficial effects of the present invention:
[0064] The photoelectric sensor prepared by the invention has good stability, good reproducibility, high detection sensitivity, wide linear range, low detection limit and strong selectivity for norfloxacin, so that the detection result has high reliability.
[0065] The photoelectric sensor provided by the present invention is combined with the nano-gold particle sol, and the electric field formed by the surface plasmon resonance accelerates the migration of electrons, enhances the optical absorption of the overall material, and improves the photoelectric response.
[0066] The photoelectric sensor provided by the present invention has a good linear relationship between the photoelectric signal intensity and the norfloxacin concentration within a certain range, can achieve effective detection of norfloxacin, and has good application value and application prospects in the fields of environment, biology and medicine. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0068] Figure 1 The figure is a diagram of the design process and application process of the photoelectric sensor in the present invention;
[0069] Figure 2 Transmission electron microscopy and energy dispersive spectroscopy characterization images, where (A) is the SEM image of the bismuth composite material modified with nano-gold particles; (B) is the EDS layered image: ad is the elemental map of the bismuth composite material after the nano-gold particles are combined; (C) is the EDS image;
[0070] Figure 3 High-resolution transmission electron microscopy characterization images: (A)-(D) are gold nanoparticles at different resolutions;
[0071] Figure 4 is the X-ray diffraction spectrum of the bismuth composite material;
[0072] Figure 5 The XPS characterization diagram of the bismuth composite material: (A) is the XPS spectrum of the bismuth composite material, proving the presence of C, O, S, Bi, and Se elements; (B) is the XPS spectrum of C 1s High-resolution XPS spectrum of O 1s High-resolution XPS spectrum of S 2p with Bi 4f High-resolution XPS spectrum of Se 3d High-resolution XPS spectra;
[0073] Figure 6 The electrochemical signal characterization diagram is shown in FIG. 1 : (A) is the IT curve diagram during the construction of the bismuth composite material photoelectric sensor modified by nano-gold particles; (B) is the EIS spectrum during the construction of the bismuth composite material photoelectric sensor modified by nano-gold particles;
[0074] Figure 7 The results of design condition optimization are shown in Figure 1. (A) is a comparison of the photocurrent responses of bismuth composite materials synthesized with different molar ratios of bismuth sulfide precursor to bismuth selenide; (B) is a comparison of the photocurrent responses of bismuth composite materials modified with nano-gold particles prepared by mixing nano-gold particles with bismuth composite materials for different ultrasonic times; (C) is a comparison of the photocurrent responses of bismuth composite materials modified with nano-gold under different applied voltages.
[0075] Figure 8The results of the investigation of selectivity, stability and sample preparation reproducibility are shown in Figure 1. (A) is the investigation of the selectivity of the photoelectric sensor, I is the photocurrent signal value of the sensor after adding different analytes, and I0 is the photocurrent signal of the blank sensor; (B) is the investigation of the temporal stability of the sensor; (C) is the investigation of the reproducibility of sample preparation of the photoelectric sensor;
[0076] Fig. 9 The analytical performance results of the photoelectric sensor for ciprofloxacin: (A) is the changing trend of the relationship between the current signal intensity of the bismuth composite material photoelectric sensor modified with nanogold particles and the concentration of norfloxacin; (B) is the linear relationship between the photocurrent signal intensity of the bismuth composite material photoelectric sensor modified with nanogold particles and the concentration of norfloxacin. DETAILED DESCRIPTION
[0077] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0078] Embodiment 1: A method for preparing a photoelectric sensor based on a bismuth sulfide composite material, comprising the following steps:
[0079] S1. Disperse 0.9 g of bismuth nitrate pentahydrate powder in 12 mL of ethylene glycol and stir ultrasonically for 10 min to obtain solution A; then disperse 0.6 g of sodium sulfide nonahydrate in 20 mL of ultrapure water and stir ultrasonically for 15 min to obtain solution B; disperse 0.65 g of urea in 10 mL of ultrapure water to obtain solution C; then gradually add 20 mL of solution B to 12 mL of solution A to form a large amount of black suspension, then add 10 mL of solution C to the above black suspension, and finally add 10 mL of solution C to the three suspensions. 1.2 g of bismuth selenide solid was added to the mixed system and stirred for 30 min; the obtained black suspension was transferred to a polytetrafluoroethylene-lined autoclave and heated at 160° C. for 8 h; after the reaction was completed, the obtained product was cooled to room temperature; the mixture was centrifuged at 4100 rpm for 10 min, the supernatant was removed, the black insoluble matter was taken, and deionized water and anhydrous ethanol were used to wash the mixture three times each, and the solid obtained after washing was placed in a 60° C. oven for drying for standby use;
[0080] S2. Prepare a 0.01% tetrahydrate chloroauric acid solution, heat it to boiling under stirring, then gradually add a 10 mM sodium citrate solution to the boiling tetrahydrate chloroauric acid solution until the solution changes from colorless to ink color, and then to purple red, then cool to room temperature, purify it with a dialysis bag with a molecular weight cutoff value of 500 Da for 22 hours, replace the water every 4 hours, and need to replace it 6 times to obtain a nano gold sol solution;
[0081] S3. Disperse 14 mg of bismuth composite material in 4 ml of nano-gold sol and disperse by ultrasonic to obtain a suspension of bismuth composite material modified by nano-gold sol; then drop 34 µL of the suspension on a fluorine-doped tin oxide glass electrode and dry at 120 °C to obtain a photoelectric sensor.
[0082] Embodiment 2: A method for preparing a photoelectric sensor based on a bismuth sulfide composite material, comprising the following steps:
[0083] S1. Disperse 1 g of bismuth nitrate pentahydrate powder in 15 mL of ethylene glycol and stir ultrasonically for 15 min to obtain solution A; then disperse 0.7 g of sodium sulfide nonahydrate in 30 mL of ultrapure water and stir ultrasonically for 20 min to obtain solution B; disperse 0.7 g of urea in 12 mL of ultrapure water to obtain solution C; then gradually add 30 mL of solution B to 15 mL of solution A to form a large amount of black suspension, then add 12 mL of solution C to the above black suspension, and finally mix the three. 1.3 g of bismuth selenide solid was added to the system and stirred for 30 min; the obtained black suspension was transferred to a polytetrafluoroethylene-lined autoclave and heated at 180° C. for 12 h; after the reaction was completed, the obtained product was cooled to room temperature; the product was centrifuged at 4300 rpm for 15 min, the supernatant was removed, the black insoluble matter was taken, and deionized water and anhydrous ethanol were used to wash it three times each, and finally the solid obtained after washing was placed in a 60° C. oven for drying for standby use;
[0084] S2. Prepare a 0.01% tetrahydrate chloroauric acid solution, heat it to boiling under stirring, then gradually add a 10 mM sodium citrate solution to the boiling tetrahydrate chloroauric acid solution until the solution changes from colorless to ink color, and then to purple red, then cool to room temperature, purify it with a dialysis bag with a molecular weight cutoff value of 500 Da for 24 hours, replace the water every 4 hours, and need to replace it 6 times to obtain a nano gold sol solution;
[0085] S3. Disperse 16 mg of bismuth composite material in 6 ml of nano-gold sol and disperse by ultrasonic to obtain a suspension of bismuth composite material modified by nano-gold sol; then drop 36 µL of the suspension on a fluorine-doped tin oxide glass electrode and dry at 120 °C to obtain a photoelectric sensor.
[0086] The prepared nano-gold-modified bismuth composite material was characterized by scanning electron microscopy (SEM), high-resolution transmission electron microscopy (TEM), energy dispersive spectroscopy (EDS), and X-ray diffraction (XRD) spectroscopy. The characterization results are as follows:
[0087] Transmission electron microscopy and energy dispersive spectroscopy characterization: Figure 2 As shown, the SEM image of the gold nanoparticle-modified bismuth composite material ( Figure 2-A) Combined with energy dispersive spectroscopy (EDS) analysis ( Figure 2 -B) It can be clearly seen that a large number of columnar bismuth sulfide partially covers the larger bulk bismuth selenide; in addition, some small clusters of nano-gold particles are interspersed near the columnar bismuth sulfide. The nano-gold particles appear as irregular spheres. It is speculated that they are combined by the gold-sulfur bonds formed between the two, which cannot be observed on the surface of bulk bismuth selenide; the above shows that the composite of nano-gold particles, bismuth sulfide and bismuth selenide is successful; in addition, energy dispersive spectrometer (EDS) analysis can reveal the elemental composition of the sample ( Figure 2 -C), EDS image of the gold nanoparticle-modified bismuth composite material, showing that the core elements such as Au, Bi, S, and Se are distributed on the surface of the prepared composite material. The insets (ad) are the contents of each element in the selected area, proving the successful synthesis of the bismuth composite material and the successful introduction of gold nanoparticles. ( Figure 2 -C) also shows the content ratio of each element in the selected area; this also strongly proves that the preparation of nano-gold modified bismuth composite materials is successful;
[0088] High-resolution transmission electron microscopy characterization: Figure 3 As shown, the composite of nano-sized bismuth sulfide and nano-gold particles can also be observed through transmission electron microscopy (TEM) images at different resolutions ( Figure 3 AD), as can be seen from the figure, the columnar bismuth sulfide is cross-linked with irregularly shaped nano-gold particles; the bismuth sulfide observed from the high-resolution transmission electron microscopy image (HR-TEM) has high crystallinity and a lattice parameter of 0.40nm ( Figure 3 -E), TEM image of nano-gold modified bismuth sulfide material also illustrates the successful combination of the two;
[0089] X-ray diffraction spectrum characterization: Figure 4 , Figure 5 As shown; Figure 4 The powder X-ray diffraction (XRD) spectrum of the bismuth composite material is shown in Figure 4-A (red line). The crystal plane parameters obtained from XRD measurements are consistent with the structure of the bismuth composite material; the synthesized product presents four diffraction peaks at 2θ=18.58°, 29.35°, 40.26° and 48.45°, which correspond to the (006), (015), (1013) and (1010) crystal planes of bismuth selenide respectively when compared with the standard XRD spectrum of bismuth selenide; there are six diffraction peaks at 2θ=23.73°, 24.92°, 27.38°, 28.64°, 32.94° and 49.09°, which correspond to the (110), (013), (102), (023), (130) and (125) crystal planes of bismuth sulfide respectively when compared with the standard XRD spectrum of bismuth sulfide; this indicates that the prepared bismuth composite material has a good crystal structure; the basic structure of bismuth sulfide and bismuth selenide is not destroyed after the composite, which also indicates the successful preparation of the bismuth composite material; in addition, Figure 5 In the study, the binding energy (BE) shift in the XPS spectrum was also used to study the intrinsic electron motion characteristics of the active interface after the structure of the bismuth composite material was formed; Figure 5 -A, elemental analysis was performed using full-range XPS scanning, and characteristic peaks of all core elements constituting the bismuth composite material were found, including S, Bi and Se; Bi4f 7 / 2 and Bi4f 5 / 2 The binding energies of Figure 5 -D), indicating that Bi exists in a trivalent state, compared with the standard binding energy of Bi4f7 of 157.0 eV. 7 / 2 The characteristic peak position shifts, which may be due to the generation of oxidized Bi (159.2 eV); the peaks at 158.1 eV and 164.6 eV are attributed to S2p3 / 2 and S2p1 / 2 ( Figure 5 -D), which is somewhat different from the standard binding energy of 163.9eV and 165.1eV, which may be caused by the stacking of the characteristic peaks of Bi4f and Se3d. This indirectly illustrates the successful preparation of bismuth sulfide. At the same time, the peaks at 54.9 and 53.9eV are attributed to Se3d 3 / 2 and Se3d 5 / 2 ( Figure 5 -E), in addition, the peak at 58.3eV corresponds to a portion of oxidized bismuth selenide, which also proves the existence of bismuth selenide;
[0090] The electrochemical signal of the prepared nano-gold-modified bismuth composite material aptamer sensor was characterized, and the characterization results are as follows:
[0091] Electrochemical signal characterization: Figure 6As shown; In order to verify whether the construction of the photoelectrochemical sensor is successful, the chronoamperometry (IT) and EIS tests are performed, as shown in Figure 6 -A, the photocurrent of the electrode modified with bismuth sulfide alone is weak (black line). When bismuth sulfide is combined with bismuth selenide to form a bismuth composite material, the photocurrent is significantly improved (green line). This may be attributed to the good carrier mobility of bismuth selenide, which makes up for the shortcomings of bismuth sulfide in this aspect. Then, the introduction of gold nanoparticles on the surface of the bismuth composite material further improves the photocurrent signal (blue line). As a good conductor of electrons, the gold nanoparticles themselves will accelerate the transfer of charges. At the same time, under the influence of visible light, the surface plasmon resonance (SPR) effect stimulated by the gold nanoparticles will further increase the absorption of visible light by the overall material, thereby making the photocurrent signal One step improvement; after the norfloxacin aptamer was modified on the surface of the nanogold-modified bismuth composite material, the photocurrent signal decreased (red line) because the large amount of negative charge it carried would hinder electrons. Correspondingly, in the electrochemical impedance spectrum, after the formation of the bismuth composite material and the introduction of nanogold particles, the electrochemical impedance of the overall electrode also gradually decreased, as shown by the gradual decrease in the radius of the semicircle (green and red marks); after the composite material was modified with the norfloxacin aptamer, the electrochemical impedance increased significantly, as shown by the significant increase in the radius of the semicircle in the figure (blue mark); the above experimental results also indirectly illustrate the successful construction of the entire photoelectrochemical sensor.
[0092] Optimization of design conditions for bismuth composite aptamer sensors modified with nano-gold:
[0093] The design condition optimization results are shown in Figure 7; in order to make the designed sensor have higher sensitivity and a wider detection range, the photocurrent signal of the designed photoelectrochemical sensor needs to be amplified as much as possible; therefore, the design of the designed photoelectrochemical sensor is optimized, mainly from the molar ratio of bismuth sulfide precursor to bismuth selenide, the ultrasonic mixing time of nano-gold particles and bismuth composite materials, and the applied voltage. The three aspects of experimental conditions are optimized to ensure that the designed photoelectrochemical sensor is under the best preparation and optimal parameter conditions; first, the molar ratio of bismuth sulfide to bismuth selenide, different amounts of bismuth selenide powder are added to a fixed amount of bismuth sulfide precursor suspension, stirred and mixed, and synthesized in one pot by hydrothermal method, and the photocurrent signal of the final bismuth composite material is investigated; from Figure 7-A It can be seen that when the molar ratio of bismuth sulfide to bismuth selenide is 1:1, the photocurrent signal of the obtained bismuth composite material is optimal. In addition, whether the amount of bismuth selenide is reduced or increased, the photocurrent signal of the prepared bismuth composite material cannot continue to increase. It is speculated that too much bismuth selenide is not conducive to the absorption of visible light by the prepared composite material, while too low an amount of bismuth selenide is not conducive to improving the carrier migration rate of the composite material; the molar concentration of the bismuth sulfide precursor is calculated based on the mass concentration of bismuth nitrate pentahydrate; then, based on the optimization of the conditions in the previous step, the condition of the ultrasonic mixing time of the nanogold particles and the bismuth composite material is optimized, such as Figure 4-7 B. When the ultrasonic duration was 2h, the photocurrent signal of the prepared nanogold-modified bismuth composite material almost reached the maximum. The subsequent extension of the ultrasonic mixing time did not have a significant effect on the overall composite material, and the generated photocurrent signal did not change significantly. The possible reason is that the concentration of the prepared nanogold particle sol is limited, and the number of nanogold particles fixed on the surface of the bismuth composite material by physical ultrasound is limited. Prolonging the time cannot increase the loading amount of nanogold particles. In order to shorten the experimental process, 2h was selected as the mixing ultrasonic duration of the final composite material. Finally, the applied voltage of the electrochemical workstation ranged from 0.1-0.5v. Figure 4-7 C can be seen that when the applied voltage is 0.1 and 0.2V, the photocurrent signal generated by the composite material is significantly higher than the photocurrent signal generated by the composite material in the applied voltage range of 0.3-0.5V; considering that the applied voltage will have an adverse effect on the surface state of the biomaterial and the photoelectrode, it was finally decided to select 0.2V as the optimal applied voltage.
[0094] Selectivity, stability and sample preparation reproducibility analysis:
[0095] Selectivity, stability and sample preparation reproducibility results are as follows Figure 8 As shown; the norfloxacin aptamer introduced during the sensor design process can specifically bind to the target, but the structure of some fluoroquinolone antibiotics is similar to that of norfloxacin, so they will bind to the norfloxacin aptamer and affect the photoelectric signal. However, some interfering substances other than these will often fall off with the rinsing of the PBS solution after co-incubation, reducing the possibility of interfering substances physically binding to the surface of the electrode material; the photocurrent signal of the blank sensor is subtracted from the photocurrent signal detected after the analyte is co-incubated with the sensor, and this difference is used as a reference. The same treatment is done for other interfering substances, and then the photoelectric signal differences corresponding to different analytes are compared; as shown Figure 8-A, it can be seen that, except for ciprofloxacin and enrofloxacin, some other interfering substances did not produce obvious responses after being incubated with the sensor; the designed sensor did not produce obvious responses to other types of antibiotics and some other substances that may be in milk, so the analysis method has good selectivity. In addition to selectivity, the stability of the photocurrent response is an important indicator reflecting the performance of the sensor. Figure 8 -B shows that the photocurrent intensity of the prepared sensor did not change significantly under 10 repeated on-off light irradiation, so it can be seen that the prepared sensor has excellent stability; in addition, in order to investigate the reproducibility of sensor sample preparation, six blank electrode samples were prepared in parallel according to the relevant experimental process, and their photocurrent signals were detected and recorded under the same conditions, such as Figure 8 -C, the test results show that the photoelectric response of the prepared sensor fluctuates almost in the range of 60-70 μA, and the RSD value is 3.2%, indicating that the constructed photoelectrochemical sensor has good reproducibility.
[0096] Analytical performance of photoelectric sensor for ciprofloxacin
[0097] The sensor's analytical performance results for ciprofloxacin are as follows: Fig. 9 As shown; Fig. 9 -A shows that as the concentration of norfloxacin increases, the IT signal gradually weakens; the results show that as the concentration of norfloxacin increases, the specific binding of norfloxacin to the norfloxacin aptamer causes its configuration to change, changing the steric hindrance. At the same time, the negatively charged norfloxacin aptamer will further repel electrons in the electrolyte solution and hinder them from flowing through the surface of the electrode, so the photocurrent has a significant downward trend; Fig. 9 -B shows the linear relationship between the logarithm of the concentration of added norfloxacin and the change value of it signal; the results show that when the norfloxacin concentration is 0.001-100ng·mL -1 Within the range, the logarithm of the concentration of norfloxacin added and the change value of the photocurrent signal show a good linear relationship. The linear regression equation is I0-I=7.5874LgC 诺氟沙星 +49.287 (R2=0.997); where I0 represents the photocurrent signal of the blank sensor during detection, and I represents the photocurrent signal detected after the sensor was incubated with different concentrations of norfloxacin.
[0098] Actual sample analysis:
[0099] Laboratory tap water and pure milk that had undergone pretreatment were used as actual samples to evaluate the feasibility of the analytical method in actual sample detection; the tap water came from the School of Pharmacy, South Campus, Shenyang Pharmaceutical University, Xihu District, Benxi City, Liaoning Province, and the pure milk was purchased from a local supermarket in Xihu District, Benxi City; considering that the content of norfloxacin in tap water and commercial milk may be low, the standard addition method was used for detection; the recovery rate RSD value was less than 2.62%. These results indicate that the prepared electrochemical sensor has good detection performance for norfloxacin in milk and tap water, is not easily interfered by the matrix, and can be used for rapid detection of norfloxacin residues in dairy products and domestic drinking water.
[0100] Table 1 Related instruments and sources
[0101] Instrument Name source DF-101S collector type constant temperature heating magnetic stirrer Gongyi Yuhua Instrument Co., Ltd. TU-1810 UV-Visible Spectrophotometer Beijing Purkinje General Instrument Co., Ltd. Thermo Fisher Nicolet 6700 Fourier Transform Infrared Spectrometer Thermo Fisher Thermo Fisher EscaLab 250Xi X-ray Photoelectron Spectrometer Thermo Fisher X-ray diffraction spectrometer Beijing Dongxi Analytical Instruments Co., Ltd. LC-400 Low Speed Centrifuge Anhui University of Science and Technology Innovation Co., Ltd. SQP-QUINTIX35-1CN electronic balance Satorius, Germany KQ-5200 Ultrasonic Cleaner Kunshan Ultrasonic Instrument Co., Ltd. Blast drying oven Tianjin Test Instrument Co., Ltd. SigMA300 Scanning Electron Microscope Zeiss Company of Germany Titan G2 60-300 Transmission Electron Microscope FEI Company CHI660E Electrochemical Workstation Shanghai Chenhua Instrument Co., Ltd. PE 950 Spectrometer PerkinElmer, USA
[0102] Table 2 Related reagents and sources
[0103] Reagent name source Sodium sulfide (analytical grade) Tianjin Hengxing Chemical Reagent Co., Ltd. Sodium citrate (analytical grade) Tianjin Hengxing Chemical Reagent Co., Ltd. Urea (analytical grade) Tianjin Hengxing Chemical Reagent Co., Ltd. Bismuth nitrate (analytical grade) Tianjin Hengxing Chemical Reagent Co., Ltd. Lactose (analytical grade) Tianjin Hengxing Chemical Reagent Co., Ltd. Bismuth selenide (purity: 98%) Shanghai MacLean Biochemical Technology Co., Ltd. Chloroauric acid tetrahydrate (0.1%) Shanghai MacLean Biochemical Technology Co., Ltd. Enrofloxacin standard (purity: 99%) Shanghai MacLean Biochemical Technology Co., Ltd. Norfloxacin standard (purity: 99%) Shanghai MacLean Biochemical Technology Co., Ltd. Ciprofloxacin standard (purity: 99%) Shanghai MacLean Biochemical Technology Co., Ltd. Potassium ferrocyanide (analytical grade) Shanghai MacLean Biochemical Technology Co., Ltd. Potassium ferrocyanide (analytical grade) Shanghai MacLean Biochemical Technology Co., Ltd. Streptomycin standard (purity: 99%) Shanghai MacLean Biochemical Technology Co., Ltd. Chlortetracycline standard (purity: 99%) Shanghai MacLean Biochemical Technology Co., Ltd. Oxytetracycline standard (purity: 99%) Shanghai MacLean Biochemical Technology Co., Ltd. 6-Mercaptohexanol (purity: 98%) Shanghai MacLean Biochemical Technology Co., Ltd. Norfloxacin Aptamer Shanghai Shenggong Bioengineering Co., Ltd.
[0104] Data Analysis:
[0105] As can be seen from Table 1, both bismuth sulfide and bismuth selenide in the present invention are semiconductor materials with excellent photoelectric properties. Bismuth sulfide has good light absorption performance in the visible light and near-infrared light ranges, and bismuth selenide is a topological insulator with high carrier mobility and good chemical stability. The present invention combines bismuth sulfide and bismuth selenide by a one-pot hydrothermal method, and mixes and incubates with nano-gold particle sol to construct a sensor for detecting norfloxacin. The sensor utilizes the optimization of carrier mobility performance after the bismuth sulfide and bismuth selenide are combined to enhance the photoelectric performance. In addition, through the combination with the nano-gold particle sol, the sensor also utilizes the surface plasmon resonance property of the nano-gold particles to enhance the optical absorption of the overall material and further improve the photoelectric response. The working principle of the entire sensor is based on the specific combination of norfloxacin and thiol-modified norfloxacin, thereby changing the steric hindrance of the electrode surface and affecting the magnitude of the current. The quantitative analysis of norfloxacin can be achieved through electrochemical technology.
[0106] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0107] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A photoelectric sensor based on a bismuth sulfide composite material, characterized in that: The preparation method of the photoelectric sensor is as follows: Step S1. Preparation of bismuth composite material; Step S2. modifying the bismuth composite material with gold nanoparticles to obtain composite material 1; Step S3. Modification of the fluorine-doped tin oxide glass electrode to obtain a modified electrode 1; Step S4. Modifying the modified electrode 1 with the norfloxacin aptamer to obtain a photoelectric sensor; The preparation process of the bismuth composite material in step S1 is as follows: Step A1. Disperse bismuth nitrate powder in ethylene glycol and stir ultrasonically for 10-15 min to obtain solution A; Step A2. Disperse sodium sulfide in ultrapure water and stir ultrasonically for 15-20 min to obtain solution B; Step A3. Dispersing urea in ultrapure water to obtain solution C; Step A4. Add solution B dropwise to solution A to form a black suspension, and then add solution C to obtain a mixed solution D; Step A5. Add bismuth selenide solid to the mixed solution D and stir for 30 min to obtain a mixed solution E; Step A6. The mixed solution E was transferred into a polytetrafluoroethylene-lined autoclave, heated at 160-180°C for 8-12h, cooled to room temperature after the reaction, centrifuged at 4100-4300rpm for 10-15min, and the supernatant was removed and washed with water and anhydrous ethanol 3 times each, and then dried in an oven at 60°C for 8-12h to obtain a bismuth composite material; The preparation process of the composite material 1 in step S2 is as follows: Step B1. Heat the tetrahydrate chloroauric acid solution to boiling under stirring, then add sodium citrate solution dropwise until the solution changes from colorless to ink color and then to purple red, cool to room temperature, and purify with a dialysis bag for 22-24 hours to obtain nano gold sol; Step B2. dispersing the bismuth composite material in the nano-gold sol, and ultrasonically dispersing the dispersed material to obtain a composite material 1; The preparation process of the modified electrode 1 in step S3 is as follows: 34-36 μL of the composite material 1 suspension was dropped onto the fluorine-doped tin oxide glass electrode and dried at 120° C. to obtain the modified electrode 1 .
2. The photoelectric sensor based on the bismuth sulfide composite material according to claim 1, characterized in that: The dosage ratio of the bismuth nitrate powder and ethylene glycol in step A1 is 0.9-1 g: 12-15 mL, and the bismuth nitrate is bismuth nitrate pentahydrate powder; The dosage ratio of sodium sulfide and ultrapure water in step A2 is 0.6-0.7 g: 20-30 mL, and the sodium sulfide is sodium sulfide nonahydrate solid; The usage ratio of urea and ultrapure water in step A3 is 0.65-0.7 g: 10-12 mL; The volume ratio of solution A, solution B and solution C in step A4 is 12-15:20-30:10-12; The usage ratio of the mixed solution D and the bismuth selenide solid in step A5 is 42-57 mL: 1.2-1.3 g.
3. The photoelectric sensor based on the bismuth sulfide composite material according to claim 1, characterized in that: The concentration of the tetrahydrate chloroauric acid solution in step B1 is 0.01%, the molecular weight cutoff MWCO of the dialysis bag is 500Da, and the water is replaced every 4 hours during the purification process, for a total of 6 times; The concentration of the sodium citrate solution is 10 mM; In step B2, the dosage ratio of the bismuth composite material to the nano-gold sol is 14-16 mg: 4-6 mL, and the ultrasonic dispersion time is 50-60 min.
4. The photoelectric sensor based on the bismuth sulfide composite material according to claim 1, characterized in that: The norfloxacin aptamer in step S4 is thiol-modified norfloxacin, and the modification process of the norfloxacin aptamer is as follows: Step C1. dissolving the norfloxacin aptamer in a buffer solution at pH=8 to obtain a mixed solution F, and incubating the mixed solution F and the modified electrode 1 at room temperature for 50-60 minutes to obtain a modified electrode 2; Step C2. drop the mixed solution F onto the surface of the modified electrode 2, and incubate at -4°C for 24 h under 100% humidity to obtain the modified electrode 3; Step C3. Incubate the surface of the modified electrode 3 with 6-mercaptohexanol, and finally rinse with a buffer solution at pH=8 to obtain a photoelectric sensor.
5. The photoelectric sensor based on the bismuth sulfide composite material according to claim 4, characterized in that: The concentration of the norfloxacin aptamer in step C1 is 100 nM; The amount of the mixed solution F in step C2 is 34-36 μL; The amount of 6-mercaptohexanol used in step C3 is 8-12 mL, and the concentration of 6-mercaptohexanol is 1 mM.
6. Use of a photoelectric sensor based on a bismuth sulfide composite material according to any one of claims 1 to 5 in the detection of norfloxacin, characterized in that: The photoelectric sensor is used to detect norfloxacin in domestic water, and the detection process is as follows: Step D1. Incubation of the photosensor and the norfloxacin aptamer; Step D2. Incubating the photosensor modified with the norfloxacin aptamer and norfloxacin; Step D3. Pre-treating the domestic water sample; Step D4. Measure the recovery rate of the sample addition.
7. Use of a photoelectric sensor based on a bismuth sulfide composite material according to any one of claims 1 to 5 in the detection of norfloxacin, characterized in that: The photoelectric sensor is used to detect norfloxacin in milk, and the detection process is as follows: Step E1. Incubation of photosensor and norfloxacin aptamer; Step E2. Incubating the photosensor modified with the norfloxacin aptamer and norfloxacin; Step E3. Sample pretreatment: pre-treat domestic water; Step E4. Measure the recovery rate of the sample addition.
Citation Information
Patent Citations
SERS-photoelectrochemical dual-mode sensor for detecting enrofloxacin as well as preparation method and application of SERS-photoelectrochemical dual-mode sensor
CN115901721A